A wireless-power and data-transfer using inductive RF link and ASK modulation - Rao, K. V. S. Subramanyeswara; Rao, G. Raja; Vaisakh, Kanchapogu (International Journal of Applied Power Engineering (IJAPE), 2024)
This paper aims to present a novel trans-cutanaeous, wireless and an efficient radio frequency (RF) inductive power and data link (IPDL) based on amplitude shift key (ASK) - modulator with an efficient ‘Class-E’– RF ‘power amplifier’ that is applicable to implantable medical devices (IMDs). The IPDL system comprises an external device placed on exterior to human skin to transmitting power and data to IMDs like implantable micro-systems (cardiac pacemakers, cochlear implants, retinal implants, deep brain stimulators) to excite and monitor respective neural and muscular system. The entire system is designed to operate with a ‘low-band-frequency’ of 4 MHz by avoiding the problem of tissue heating. A practical model for the IPDL with results is presented. Various graphs such as frequency vs primary coil/secondary coil output are plotted and shown. Typical specifications of the exterior device, namely, the modulation-index (MI) and the modulation-rate (MR) are 40% and 4.3% respectively with a data rate of 172 Kbps. The design is simulated with electronic workbench MULTISIM 12.0 and TINA Ver 9.